Macro- and microplastic accumulation in soil after 32 years of plastic film mulching. (1st May 2022) - Li, Shitong; Ding, Fan; Flury, Markus; Wang, Zhan; Xu, Li; Li, Shuangyi; Jones, Davey L.; Wang, Jingkuan
Abstract: Plastic film mulch (PFM) is a double-edged-sword agricultural technology, which greatly improves global agricultural production but can also cause severe plastic pollution of the environment. Here, we characterized and quantified the amount of macro- and micro-plastics accumulated after 32 years of continuous plastic mulch film use in an agricultural field. An interactive field trial was established in 1987, where the effect of plastic mulching and N fertilization on maize yield was investigated. We assessed the abundance and type of macroplastics (>5 mm) at 0–20 cm soil depth and microplastic (<5 mm) at 0–100 cm depth. In the PFM plot, we found about 10 times more macroplastic particles in the fertilized plots than in the non-fertilized plots (6796 vs 653 pieces/m 2 ), and the amount of film microplastics was about twice as abundant in the fertilized plots than in the non-fertilized plots (3.7 × 10 6 vs 2.2 × 10 6 particles/kg soil). These differences can be explained by entanglement of plastics with plant roots and stems, which made it more difficult to remove plastic film after harvest. Macroplastics consisted mainly of films, while microplastics consisted of films, fibers, and granules, with the films being identified as polyethylene originating from the plastic mulch films. Plastic mulch films contributed 33%–56% to the total microplastics in 0–100 cm depth. The total number of microplastics in the topsoil (0–10 cm) ranged as 7183–10, 586 particles/kg, with an average of 8885 particles/kg. In the deep subsoil (80–100 cm) the plastic concentration ranged as 2268–3529 particles/kg, with an average of 2899 particles/kg. Long-term use of plastic mulch films caused considerable pollution of not only surface, but also subsurface soil. Migration of plastic to deeper soil layers makes removal and remediation more difficult, implying that the plastic pollution legacy will remain in soil for centuries. Graphical abstract: Image 1 Highlights: N fertilization aggravated the abundance of macroplastic and film microplastic. Microplastics consisted of films, fibers, and granules in long film-mulched soil. Film microplastic was identified as originating from the plastic mulch films. Plastic film-derived microplastics can readily migrate down the soil profile. Plastic films contributed 33%–56% to total microplastics for 0–100 cm profile.